A comprehensive review of the ethnomedicine, phytochemistry, pharmacological activities of the genus Kniphofia - Gashaw Nigussie; Metasebia Tegegn; Dessalegn Abeje; Haregua Melak (Taylor & Francis Group, 2022)
Context Kniphofia (Asphodelaceae) is found mainly in South Africa and Tropical Africa. Malaria, hepatitis B, blood purifier, cancer, eczema, and female infertility have all been traditionally treated using this genus.Objective The current review provides a complete and up-to-date compilation of documented traditional medicinal uses, phytochemicals, and pharmacological activities of the genus.Method Relevant literature was collected by searching the major electronic scientific databases including PubMed, Science Direct, Web of Science, and Google Scholar using appropriate keywords ethnomedicinal studies, phytochemical investigations, and pharmacological activities of Kniphofia species. The search strategy included all articles with descriptors that were available until November 30, 2021. Only published works in English were used for this study. The data were collected using textual descriptions of the studies, tabulation, grouping, and figures.Result At present, more than 40 compounds have been isolated from different parts of Kniphofia species. The major compounds isolated from the Kniphofia species are monomeric anthraquinones and dimeric anthraquinones. Pharmacologically the extracts and isolated compounds showed antioxidant, antimalarial, antiproliferative, anti-HIV-1, anti-leukotriene, and cytotoxic activity. The genus afforded exemplary drug leads such as knipholone and knipholone anthrone with anti-HIV-1, antimalarial and cytotoxicity activity.Conclusions Kniphofia species have traditionally been used to treat a variety of diseases. Pharmacological actions of phytochemicals were shown to be promising. Despite this, considering the genus's inclusion on the red data list of South Africa, it deserves more attention. In order to find novel drug candidates, more studies on promising crude extracts and compounds are needed.